SUSTAINABLE INCLUSIVE DEVELOPMENT OF TERRITORIAL COMMUNITIES OF VOLYN REGION IN THE CONDITIONS OF TRANSFORMATION COAL INDUSTRY (Economic journal of Lesya Ukrainka Volyn National University, 2022)
Annotation: Peculiarities of formation and implementation of economic policy in the field of coal industry of territorial communities of Volyn region are considered, in particular in the part of strategic plans - programs of social and economic development, which are focused on intensification of business activity.The main factor in the development of economic potential of territorial communities of Volyn region is natural resource potential and its economic effect in terms of increasing production and increasing profits of various organizational and legal forms of ownership of the social effect in terms of creating new jobs, providing employment, leads to poverty population.The analysis of the coal - industrial complex in the Volyn region and the dependence between the indicators of socio - economic development of territorial communities is carried out. Budgetary mechanisms for ensuring the State Target Program for Fair Transformation of Coal Regions are considered. Consider the prospects of including certain communities in the list of territories defined in paragraph 68 of subsection 10 of section XX "Transitional Provisions" of the Tax Code of Ukraine on the exemption of newly formed entities from the processing industry from paying certain taxes.The analysis shows that effective development requires the implementation of strategic management as a prerequisite for improving the efficiency of the coal industry and ensuring the economic growth of various structures in market conditions. Achievements, problems and tasks for further effective development of the coal industry in Volyn region are revealed. It is proposed to use one of the strategic directions of achieving the goals of sustainable development to implement a long-term comprehensive development strategy that will contain organizational, economic and financial principles of ensuring the welfare of local communities, improving budgetary mechanisms; stimulating the inhabitants of the territorial community to ensure their own well-being and intensification of local economic development by activating the economic potential.
Keywords: coal industry, mines, territorial communities, transformation of coal regions, tax capacity, rural areas